Alat Peraga Kendali Pemanas Udara Berbasis Arduino Uno Sebagai Penunjang Praktikum Laboratorium Kendali Politeknik Negeri Semarang [A Demonstration Tool of Arduino Based Air Heater Controller to Support Control Laboratory of Politeknik Negeri Semarang] - Supriyo, Bambang; Kuntardjo, Samuel Beta; Sihono, Sihono (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2017)
The objective of this research is to develop and test the demonstration tool of Arduino based air heater controller with Proportional Integral Derivative (PID) based control methods for the temperature range between 50ºC and 70ºC.   Arduino Uno was programmed using C-language to do control tasks and to transfer control data serially to computer via USB port. The selection of the initial PID  parameters are determined using the combination of Relay Feedback method and Ziegler-Nichols  formula.  The control methods were focused on proportional (P), proportional derivative (PD) dan Proportional Integral Derivative (PID) with the performance criteria based on overshoot  dan steady state error.  The experimental results show that the PID controllers give best output responses in terms of zero steady state errors, while P and PD controllers still result in steady state errors of about 3ºC. In addition, P controllers still give about 2,5ºC-4ºC fluctuative output values below set points, while the PD and PID have very small fluctuative values and even very close to zero. This laboratory demonstration tool has shown very good PID based controller performance, so it is feasible to be used as a supporting demonstration tool for control system laboratory in Politeknik Negeri Semarang or even other universities.